APLIKASI DATA MINING UNTUK PENILAIAN KREDIT MENGGUNAKAN DECISION TREE ALGORITMA ID3 STUDI KASUS PT. MANDALA MULTI FINANCE CABANG KENDARI - Ilayani, Ilayani; Nangi, Jumadil; Pasrun, Yuwanda Purnamasari (Informatics Engineering Department of Halu Oleo University, 2018)
Credit is one of the most common payment mechanisms in the community. Data mining can search the pattern and new knowledge of these data so that it can facilitate in determination of debtor candidate. For that required a data mining applications that can process and provide the decision of the prospective debtor's eligibility status automatically. One method of data mining used for the classification of prospective borrowers is the decision tree using Iterative Algorithm Dichotomiser 3 (ID3).ID3 is one of the most popular types of Decision trees that attempt to build a decision tree top-down, starting with the first attribute to be checked and placed as root. The ID3 or Iterative Dichotomiser 3 algorithm is a method used to produce decision trees that are able to classify an object. Attributes used are file, job, character, address, pay slip, and motor price.Based on the test results, ID3 method can be implemented in credit appraisal application for the determination of eligibility with 100% accuracy value for 10 data testing from 100 training data and 30 data testing from 60 training data.Keywordsâ€”Credit, Data Mining, Decision Tree, ID3Â DOI :Â 10.5281/zenodo.1402830